Право виконавців і виробників фонограми на справедливу винагороду - Троцька, Валентина; Trotska, Valentyna (Видавництво Львівської політехніки, 2025)
Стаття присвячена питанням виплати виконавцям творів та виробникам фоно- грам винагороди, яку прийнято називати справедливою, за використання фонограм і зафіксованих у них виконань. Визначено причини запровадження права на справедливу винагороду для вико- навців і виробників фонограм у міжнародному, європейському та національному зако- нодавствах. Доведено, що у законодавстві визначення поняття “справедлива винаго- рода” немає, хоча цей термін широко використовується у сфері авторського права і суміжних прав. На основі правового аналізу законодавства встановлено відмінність між поняття- ми “винагорода” і “справедлива винагорода”. Обґрунтовано, що ототожнення цих по- нять у Законі України “Про авторське право і суміжні права” призвело до появи протиріч, неузгодженостей між його нормами, що істотно знижує якість законодавства та позначається на практиці його застосування. У зв’язку з цим виокремлено основні ознаки, притаманні цьому терміну, та сформульовано авторське визначення поняття “справедлива винагорода”. Опрацьовано норми Закону, що передбачають право на справедливу винагороду за: 1) використання виконань і фонограм, створених працівниками (виконавцями, ви- робниками фонограм) за трудовим договором; 2) публічне виконання; передачу в ефір фонограми і виконання, зафіксованого у фонограмі, опублікованих з комерційною ме- тою; 3) приватне копіювання фонограми і виконання, зафіксованого у фонограмі; 4) прокат примірників. Доведено, що норми Закону, що стосуються права на справедливу винагоро- ду, потребують удосконалення. На основі проведеного правового аналізу запропоновані зміни і доповнення до Закону України “Про авторське право і суміжні права” та інших законів. Підкреслено, що внесення змін і доповнень до законодавства надасть правової визначеності, передбачуваності нормам, що сприятиме їх ефективній реалізації на практиці.

The article examines the features of a payment of the remuneration, which is called “equitable”, “fair” or “fair compensation”, for the use of phonograms and performances recorded in them. It is noted that the right to equitable remuneration is not new, it is known under international and European law. The author analyses the reasons for the introduction of the right to equitable remuneration for performers and phonogram producers in international, European and national legislation. The article is based on the legal analysis of the norms of the Law of Ukraine “On Copyright and Related Rights” and other laws relating to the payment of equitable remuneration. Based on the legal analysis of international, European and national legislation, the author describes the difference between the terms of “the remuneration” and “the equitable remuneration”. The author proves that these terms are not identical. International, European and Ukrainian legislation does not define the term of “equitable remuneration”, although it is widely used. In this regard, the author analyses the main features inherent in this term and formulates the author’s definition of the term “equitable remuneration”. The article examines the norms in the Law, which provide for the right to equitable remuneration for: 1) use of performances and phonograms created by employees (performers, phonogram producers) under an employment contract; 2) public performance; broadcasting of a phonogram and performance recorded in a phonogram, published for commercial purposes; 3) private copying of a phonogram and performance recorded in a phonogram; 4) rental of the copies. The author proves that there are the inconsistencies in the Law and other the shortcomings that need to be eliminated for the effective implementation of the provisions in a practice. The author proposes amendments and additions to the Law of Ukraine “On Copyright and Related Rights” and other laws. Аmendments and additions to the legislation will provide legal certainty to the norms, which will facilitate their effective implementation in the context of receiving equitable remuneration by performers and phonogram producers and its payment by users.
The right of performers and phonogram producers to equitable remuneration
Keywords: інтелектуальна власність; авторське право; суміжні права; спра- ведлива винагорода; виконавці; виробники фонограми; intellectual property; copyright; related rights; equitable remuneration; performers; phonogram producers; 347.785